Frequency and characteristics of substance use among university students in trnc - Özsat, Kübra; Işıktaş, Serdal (Journal of Dependence, 2024)
Objective: This study aimed to explore the prevalence and attributes of substance use among university students. Method: The study sample comprised 1,500 university students enrolled in TRNC during the academic year 2022-2023, selected via random sampling. Data collection utilized the Sociodemographic Information Form and the Addiction Profile Index Scale (API). Results: Alcohol use exhibited a higher prevalence compared to other substances in this study, followed by marijuana, heroin, and other substances. Male participants displayed higher addiction severity total scores, substance use characteristics, diagnosis impacts on life, severe craving, and motivation subscale scores than females. Participants aged between 18 and 24 showed lower addiction severity total scores and all sub-dimension scores compared to other age cohorts. Addiction severity scores, substance use characteristics, diagnosis, severe craving, effects on life, and motivation sub-dimension scores varied significantly based on participants’ socio-economic levels Mean addiction severity scores were notably lower among individuals with migration experience compared to those without. Conclusion: Gender, age, socio-economic status, migration experience, and psychological/psychiatric treatment history significantly influenced mean addiction severity scores. The findings underscores the importance of supporting university students through programs fostering effective behaviors and life skills at a younger age, alongside early preventive initiatives targeting risky behaviors such as substance use.